Epidemiology and Characteristics of Neurosurgical Conditions at Mbarara Regional Referral Hospital - Abdelgadir, Jihad; Smith, Emily R.; Punchak, Maria; Vissoci, Joao Ricardo; Staton, Catherine; Muhindo, Alex; Kitya, David; Park, Lawrence P; Haglund, Michael M. (World neurosurgery, 2017)
Background: The unmet surgical need, specifically neurosurgical need, in Uganda is significant, yet only two public hospitals currently perform neurosurgery in the country. This study examines the epidemiology and outcomes of neurosurgical conditions presenting to one of regional referral hospitals in Uganda, in an effort to understand the neurosurgical needs of this population. Methods: The study was conducted at Mbarara Regional Referral Hospital (MRRH), in southwestern Uganda. Demographics, clinical characteristics and outcomes were retrospectively collected for all patients that presented to MRRH with a neurosurgical condition between January 2012 to September 2015. Results: During the study period, 1854 patients presented to MRRH with a neurosurgical condition. Over 50% of patients were between 19 and 40 years old and the majority of were males (76.1%). The overall median length of stay was 5 days (IQR: 2.5-10). The majority of admissions were due to trauma (87%), with almost 60% due to road traffic incidents (RTIs). The overall mortality rate was 12.8%. A multivariable Cox proportional hazards model revealed that age, closed head injury and admission GCS have a strong positive correlation with mortality while getting a diagnostic image and neurosurgical procedure were negatively correlated with mortality. Conclusion: Traumatic brain injury (TBI) represented the majority of neurosurgical admissions at MRRH, disproportionately affecting young males. Age, closed head injury, admission GCS, getting a diagnostic image and neurosurgical procedure were all independent predictors of mortality. Resource appropriate interventions throughout the health system are needed to meet the demand and improve outcomes.
Keywords: Epidemiology; Surgical need; Uganda; Neurosurgery